Mixed-reality-based human-animal interaction can relieve mental stress - Na, Heewon; Dong, Suh-Yeon (Frontiers in Veterinary Science, 2023)
Interacting with animals has been demonstrated to possess the healing benefits to humans. However, there are limitations in physical interaction due to COVID-19 and safety issues. Therefore, as an alternative, we created mixed-reality (MR) -based human-animal interaction (HAI) content and experimentally verified its effect on mental stress reduction. We created three types of interactive content: observing the movement of a non-reactive virtual cat, interacting with a virtual cat whose responses can be seen, and interacting with a virtual cat whose responses can be both seen and heard. The experiment was performed by 30 healthy young women, and a mental arithmetic task was used to induce mild mental stress before experiencing each content. During the experiment, the subject’s electrocardiogram was continuously recorded, and the psychological state was evaluated through a questionnaire. The results showed that MR-based virtual cat content significantly reduces mental stress and induces positive emotions after stressful situations. In particular, when the virtual cat provided audiovisual feedback, the activation amount of the parasympathetic nervous system and the increase of positive emotions were the greatest. Based on this encouraging research result, this method should be further investigated to see if it can replace real HAI for human mental health management.